Discovery Learning Model with Ethnopedagogy Approach in Improving Students' Comprehension Ability - Subekhi, Muhammad Imam; Fakhruddin; Sulistyorini, Sri (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
This research objective is to analyze a validity of device and effectiveness of learning discovery learning with ethno pedagogy approaches to improve learners’ understanding concepts. Kinds of this research is quantitative approach by applying quasi experimental designs. While this research population was VI grade learners of SD Dewi Sartika Cluster, Annual District, Jawa Tengah. The results of the analysis of students' conceptual understanding abilities show that there are differences in the improvement in classes that apply the Discovery Learning learning model with an ethnopedagogical approach. The average increase in the N-Gain understanding of students' concepts in the pretest and posttest in the experimental class was 0.54 while the control class was 0.36. The application of Discovery Learning with an ethnopedagogical approach can be concluded to further improve students' understanding of concepts. The learning delivered becomes interesting with the involvement of students in learning. In addition, the application of Discovery Learning with an ethnopedagogical approach is able to make the learning process more active and fun. This study can be concluded that learning Discovery Learning with an ethnopedagogical approach in improving students' understanding of concepts is valid and effective. The results of this study can be used as information material to pay attention to the appropriate learning model for learning nuanced with local wisdom.
Keywords: Discovery Learning; Ethnopedagogy; Students' Comprehension Ability